THE CONCEPT OF RECIPROCITY IN ISLAMIC ECONOMICS: AN ANTHROPOLOGICAL APPROACH - Pungky Lela Saputri; M Fatchurrohman (JASIE, 2022)
This paper aims to find out the concept of reciprocity in Islamic economics through anthropological approach. The method used in this research is qualitative with the approach of library studies. This literature study is considered capable of reviewing the concept of reciprocity in Islamic economics through anthropology. In reciprocity, an individual or group delivers goods or services to another individual or group without specifying a time limit on return. In the Context of Islam, man arofa nafsahu faqod arofa robbahu, if practiced in real time then all human behavior in the economic world becomes very easy to control, and the controller is every human being himself.